The impact of cumin seed extracts with antifungal properties on Candida albicans and adhesion resistance in soft denture liners - Nour, Ayat Naseer Abdul; Rashid, Amal Abdul Latif; Al-Saadi, Adel Saadi (Brazilian Dental Science, 2025)
Objective: Soft liner materials, while beneficial for denture stability, often harbor fungal growth, particularly at sites where the bond between denture base and the liner weakens, creating favorable conditions for colonization by C. albicans. Herbal plant extracts offer a novel therapeutic approach due to their antifungal properties, which are typically safer and associated with fewer side effects compared to conventional antifungal drugs. This study aims to evaluate the antifungal impact of ethanol and oil extracts of cumin seeds and their impact on the shear bond strength of soft denture liners. Material and Methods: C. albicans strains were isolated and identified. Extracts of cumin seeds (ethanol and oil) were prepared and evaluated for their antifungal activity using microdilution tests. Thirty specimens of soft lining material were prepared for testing shear bond strength testing using a Universal Instron machine, both with and without cumin extracts incorporation. Results: Both ethanol and oil extracts of cumin demonstrated inhibition of C. albicans growth. Significant increases in shear bond strength were observed with ethanol cumin extract in comparison to the control group, whereas the oil cumin extract did not significantly affect shear bond strength. Conclusion: Oil and ethanol extracts from cumin seeds exhibit antifungal properties versus C. albicans. While ethanol extract enhances shear bond strength, the oil extract shows no significant impact on bond strength. These findings highlight the potential of ethanol cumin extract as a dual-function material for enhancing denture hygiene and mechanical stability. KEYWORDS Antifungal; Cumin extracts; Shear; Soft liners; Strength.